Resource endowment and sustainable soil fertility management strategies in maize farming systems in northern Benin - Tovihoudji, Pierre G.; Sossa, Elvire Line; Egah, Janvier; Agbangba, Emile C.; Akponikpè, P. B. Irenikatché; Yabi, Jacob A. (Frontiers in Sustainable Resource Management, 2024)
Introduction Managing soil fertility remains one of the major concerns of smallholder farmers in Sub-Saharan Africa (SSA). In order to understand the adoption potential of recommended practices to smallholders, this study aimed to characterize the resource availability, allocation and use patterns, and the soil fertility management practices in the maize farming system in northern Benin. Methods A survey was conducted with 262 households randomly selected across three municipalities from three agro-ecological zones. Focus groups discussions and individual interviews were conducted with the household heads using an interview guide and a structured questionnaire respectively. The main data collected included (a) the socio-economic characteristics of households, (b) the main farm type and their characteristics and (c) the current soil fertility management strategies and the rationale behind. Results and discussion The main soil fertility practices included the use of mineral fertilizer, manure, and crop residues application to plots. As a general trend, the rates of fertilizers applied by farmers [on average 132 ± 8.5 and 59 ± 5.8 kg ha−1 of Nitrogen-Phosphorus-Potassium (NPK) and urea] were below those recommended or required to ensure optimal maize yields. Five farm types corresponding to different resource endowments or wealth classes were identified. The scarce resource farms owned by the majority of poorer farmers use only small amounts of manure and fertilizer in their fields. Qualitative analysis indicated that farms have different constraints and opportunities to adopt newly proposed soil fertility management recommendations. Conclusion Extension services and decision makers must target specific interventions for appropriation and sustainability of technologies to resource mostly the smallholder farmers.